2019
DOI: 10.1073/pnas.1904978116
|View full text |Cite
|
Sign up to set email alerts
|

Histone H4 induces platelet ballooning and microparticle release during trauma hemorrhage

Abstract: Trauma hemorrhage is a leading cause of death and disability worldwide. Platelets are fundamental to primary hemostasis, but become profoundly dysfunctional in critically injured patients by an unknown mechanism, contributing to an acute coagulopathy which exacerbates bleeding and increases mortality. The objective of this study was to elucidate the mechanism of platelet dysfunction in critically injured patients. We found that circulating platelets are transformed into procoagulant balloons within minutes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
93
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 46 publications
5
93
0
1
Order By: Relevance
“…16,24 However, a recent study of patients with TIC in which platelet function was measured by multiple assays including aggregometry, surface receptor expression, platelet mapping, and platelet function analyzer suggests that, in fact, platelets from patients with TIC retain their secretory function despite evidence of impaired aggregation. 16 Others have identified that inhibitory factors in the plasma of trauma patients may be driving platelet dysfunction 25 or may even lead to changes in platelet morphology and structure leading to subsequent destruction, 26 but the clinical implications of impaired platelet aggregation in the setting of injury remain controversial. While multiple studies have demonstrated strong associations between impaired platelet aggregation and up to 10-fold higher mortality rates, 8,9,21 others have shown that even minor injuries represented by low median ISS scores of 5 can result in platelet inhibition, questioning the clinical relevance of these findings.…”
Section: Discussionmentioning
confidence: 99%
“…16,24 However, a recent study of patients with TIC in which platelet function was measured by multiple assays including aggregometry, surface receptor expression, platelet mapping, and platelet function analyzer suggests that, in fact, platelets from patients with TIC retain their secretory function despite evidence of impaired aggregation. 16 Others have identified that inhibitory factors in the plasma of trauma patients may be driving platelet dysfunction 25 or may even lead to changes in platelet morphology and structure leading to subsequent destruction, 26 but the clinical implications of impaired platelet aggregation in the setting of injury remain controversial. While multiple studies have demonstrated strong associations between impaired platelet aggregation and up to 10-fold higher mortality rates, 8,9,21 others have shown that even minor injuries represented by low median ISS scores of 5 can result in platelet inhibition, questioning the clinical relevance of these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets from patients with immune thrombocytopenia have increased (apoptosis-induced) PS exposure likely contributing to the decreased platelet counts (128,129). Recently, there has been the report of increased circulating PS-exposing ballooned platelets in trauma hemorrhage in response to the damage-associated molecular pattern histone H4, demonstrating a mechanism by which platelets respond to tissue damage (130).…”
Section: Pathologies Of Phosphatidylserine Exposurementioning
confidence: 99%
“…Trauma-induced coagulopathy is characterized by platelet dysfunction. 1,2 Whereas platelet counts can be preserved during traumatic bleeding, platelet dysfunction occurs in approximately 45% of trauma patients. [1][2][3] In accordance, transfusion of high doses of platelets results in a reduction in early death following trauma compared to lower doses of platelets.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Whereas platelet counts can be preserved during traumatic bleeding, platelet dysfunction occurs in approximately 45% of trauma patients. [1][2][3] In accordance, transfusion of high doses of platelets results in a reduction in early death following trauma compared to lower doses of platelets. 4,5 Liquid stored platelet products however, have a limited shelf-life (5-7 days at room temperature).…”
Section: Introductionmentioning
confidence: 99%